Comprehensive analysis of RFC4 as a potential biomarker for regulating the immune microenvironment and predicting immune therapy response in lung adenocarcinoma - Zheng, Jianqing; Lin, Na; Huang, Bifen; Wu, Min; Xiao, Lihua; Zeng, Bingwei (Frontiers in Immunology, 2025)
BackgroundReplication factor C subunit 4 (RFC4) is crucial for initiating DNA replication via DNA polymerase δ and ϵ and is overexpressed in various cancers. However, its relationship with the tumor immune microenvironment (TIME), and immunotherapy response in lung adenocarcinoma (LUAD) remains unclear. This study aimed to determine whether overexpressed RFC4 impacts survival in patients with LUAD and to explore potential mechanisms of RFC4 in regulating the TIME using integrated bioinformatics.MethodsLUAD gene expression data were downloaded from the Cancer Genome Atlas (TCGA) database and used for exploratory analysis. Differential expression of RFC4 was validated using gene expression data from the Gene Expression Omnibus (GEO). Clinical data with survival information from TCGA and GEO were use to explore and validate the prognostic value of RFC4. The relationship between RFC4 and TIME was studied by Cell-type identification by estimating relative subsets of RNA transcripts (CIBERSORT) and Estimation of Stromal and Immune cells in Malignant Tumor tissues using Expression data (ESTIMATE). Tumor Immune Dysfunction and Exclusion (TIDE) was used to predict the therapeutic response of RFC4 to immune checkpoint inhibitors. We validated the differential expression of RFC4 in LUAD and adjacent tissues using immunohistochemical staining in a real-world cohort from the Second Affiliated Hospital of Fujian Medical University.ResultsRFC4 was significantly over-expressed in LUAD at both the RNA and protein levels. High RFC4 expression levels were associated with poor prognosis in LUAD, both in TCGA and GEO. High RFC4 levels were significantly associated with immunostimulators and immune cells infiltration in LUAD tissues. Correlation analysis revealed a significant relationship between the RFC4 and ESTIMATE scores. A high RFC4 expression level was associated with a lower TIDE score, indicating a stronger therapeutic response to immunotherapy. Functional prediction of RFC4 suggested that RFC4 mainly participated in DNA replication and repair, and reshaped the TIME.ConclusionsRFC4 proved to be a promising biomarker for tumorigenesis and could effectively predict immunotherapy response in LUAD. RCF4 altered tumor prognosis by reshaping the TIME, and targeted inhibition of RCF4 may be a promising new strategy for treating LUAD.